Propaganda image of the social world in Polish children’s songs - Małgorzata Pilecka (Problemy Wczesnej Edukacji)
The aim of this paper is to present results of critical analyses of Polish children’s songs. Having analysed the lyrics of more than eighty Polish children’s songs, the author couched main categories construing the image of the social world presented in them. The qualitative research revealed propaganda role of the language used in children’s songs: the features of social world (i.e. people, places, relationships, behaviours and values) that are presented in these songs often transmit strongly stereotypical and oversimplified vision of the social reality. In this sense, social education is based on manipulation in which lyrics are the main tool of symbolic violence.